Effect of Clay Minerals on Carbonate Precipitation Induced by Cyanobacterium Synechococcus sp. - Xiao Wang; Xiangxin Kong; Qian Liu; Kun Li; Zaixing Jiang; Hengjun Gai; Meng Xiao (Microbiology Spectrum, 2023)
ABSTRACT Carbonate precipitation induced by cyanobacteria is an important factor in lacustrine fine-grained carbonate rock genesis. As key components of these rocks, clay minerals play an important role in aggregating cyanobacteria. However, the formation mechanism of fine-grained carbonate under the effect of clay minerals is unclear. In this study, we investigated carbonate precipitation by Synechococcus cells under the influence of clay minerals. The results showed that clay minerals can accelerate Synechococcus aggregation, and the aggregation rate of the kaolinite group was significantly higher than that of montmorillonite. The aggregate size and Synechococcus cell content increased with an increase in clay minerals, resulting in increasing organic matter and carboxyl content in the aggregates. Due to the high affinity between carboxyl and Ca2+, the presence of Synechococcus sp. could improve the Mg/Ca molar ratio in the microenvironment of aggregates, which is conducive to aragonite precipitation. Thus, aragonite 5 to 10 μm in size precipitated when Synechococcus and clay minerals coexisted, whereas low-magnesium calcite (15 to 60 μm) was the main carbonate only in the presence of Synechococcus. This study provides important insights into the mechanisms of microbial-induced carbonate precipitation under the effect of clay minerals, which might offer theoretical support for the genesis of fine-grained lacustrine carbonate. IMPORTANCE The biogenesis of lacustrine fine-grained carbonates is of great significance to the exploitation of shale oil. Clay minerals are an important component of lacustrine fine-grained sedimentary rocks, which is conductive to the aggregation and settlement of cyanobacteria. We investigated the precipitation of carbonate induced by Synechococcus sp. with the addition of kaolinite and montmorillonite. The pH and calcium carbonate saturation of the environment increased under the effect of cyanobacteria photosynthesis. The aggregation of cyanobacteria cells increased the Mg/Ca molar ratio of the microenvironment, creating a favorable condition for the precipitation of aragonite, which was similar in size to the micritic calcite of fine-grained sedimentary rocks. This study provides theoretical support for the genesis of fine-grained carbonates.